'Deliberative development': Australia's Baugruppen movement and the challenge of greater social inclusion. Issue 1 (2nd January 2020) - Sharam, Andrea
Abstract: German Baugruppen are the most well-known of the collaborative, self-organized alternatives to speculatively produced multi-residential housing, delivering housing at a significant price discount to market. However, Baugruppen have been criticized for excluding less affluent households with financing and social capital barriers identified by Hamiduddin and Gallent as reinforcing socio-economic stratification. Collaborative, self-organized housing is, however, under-researched and there has been scant attention to financing. Collaborative, self-organized multi-residential housing in Australia is known as 'deliberative' development to differentiate it from 'speculative' development. We draw on case studies of deliberative development in Australia to reveal how projects are financed and how financing impacts on social equity considerations. Proponents of contemporary deliberative development in Australia are deeply concerned about housing affordability and declining rates of home ownership. This has focused attention on development financing as a key to systemic change paving the way for inclusion of less wealthy households.